Eugene P. Kennedy’s Legacy: Defining Bacterial Phospholipid Pathways and Function - Dowhan, William; Bogdanov, Mikhail (Frontiers in Molecular Biosciences, 2021)
In the 1950’s and 1960’s Eugene P. Kennedy laid out the blueprint for phospholipid biosynthesis in somatic cells and Escherichia coli, which have been coined the Kennedy Pathways for phospholipid biosynthesis. His research group continued to make seminal contributions in the area of phospholipids until his retirement in the early 1990’s. During these years he mentored many young scientists that continued to build on his early discoveries and who also mentored additional scientists that continue to make important contributions in areas related to phospholipids and membrane biogenesis. This review will focus on the initial E. coli Kennedy Pathways and how his early contributions have laid the foundation for our current understanding of bacterial phospholipid genetics, biochemistry and function as carried on by his scientific progeny and others who have been inspired to study microbial phospholipids.